Carpathian Basin and the Development of the Hungarian Landscape Theory Until 1948 - Hajdú, Zoltán (Discussion Papers, 2012)
The study provides a comprehensive overview of Hungarian landscape theory, the notion and concept of the Carpathian basin, territorial delimitation and the interactions between them. The theory is challenged by the fact that theoretical categories and constructions have become a subject of applied research, since parties with conflicting interests do not question the given spatial category alone but the theory itself as well.